Nano-Mechanical Properties of Surface Layers of Polyethylene Modified by Irradiation - Ovsik, Martin; Manas, Miroslav; Stanek, Michal; Dockal, Adam; Mizera, Ales; Fluxa, Petr; Bednarik, Martin; Adamek, Milan (Materials (Basel, Switzerland), 2020)
This study's goal was to describe the influence of a wide range of ionizing beta radiation upon the changes in surface layer mechanical properties and structural modifications of selected types of polymer. Radiation crosslinking is a process whereby the impingement of high-energy electrons adjusts test sample structures, thus enhancing the useful properties of the material, e.g., hardness, wear-resistance, and creep, in order that they may function properly during their technical use. The selected polymers tested were polyolefin polymers like polyethylene (Low-density polyethylene LDPE, High-density polyethylene HDPE). These samples underwent exposure to electron radiation of differing dosages (33, 66, 99, 132, 165, and 198 kGy). After the crosslinking process, the samples underwent testing of the nano-mechanical properties of their surface layers. This was done by means of a state-of-the-art indentation technique, i.e., depth-sensing indentation (DSI), which detects the immediate change in the indentation depth associated with the applied force. Indeed, the results indicated that the optimal radiation dosage increased the mechanical properties by up to 57%; however, the beneficial levels of radiation varied with each material. Furthermore, these modifications faced examination from the structural perspective. For this purpose, a gel test, Raman spectroscopy, and crystalline portion determination by X-ray all confirmed the assumed trends.
Keywords: polymers; spectroscopy; X-ray; crosslinking; gel content; nano-indentation; electron rays